2006
DOI: 10.1158/0008-5472.can-05-1381
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Double Minute 2 Associates with Chromatin in the Presence of p53 and Is Released to Facilitate Activation of Transcription

Abstract: The tumor suppressor p53 is a potent transcription factor of which the ability to mediate transcription is inhibited through an interaction with the oncoprotein mouse double minute 2 (Mdm2). The present study has tested the hypothesis that Mdm2 inhibits the p53 response in normally growing cells by binding to chromatin-associated p53. Using chromatin immunoprecipitation, we show that Mdm2 localizes with p53 at its responsive elements on the waf1 and mdm2 genes in human cell lines expressing p53, but not in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…However, several studies reported detection of MDM2 binding to p53 target gene promoters, indicating that the MDM2-p53 complex has DNA binding activity in vivo (45)(46)(47)(48)(49). To further investigate the effect of MDM2 on p53 DNA binding, we purified MDM2-p53 complex from H1299 cells cotransfected with p53 and FLAG-MDM2 using M2 beads for pulldown and FLAG peptide for elution.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies reported detection of MDM2 binding to p53 target gene promoters, indicating that the MDM2-p53 complex has DNA binding activity in vivo (45)(46)(47)(48)(49). To further investigate the effect of MDM2 on p53 DNA binding, we purified MDM2-p53 complex from H1299 cells cotransfected with p53 and FLAG-MDM2 using M2 beads for pulldown and FLAG peptide for elution.…”
Section: Resultsmentioning
confidence: 99%
“…A third possibility is that genotoxic stress induces various p53 cofactors, which can contribute to p53 specificity. Indeed, recent experiments have shown that p53 activation of certain genes is affected by cofactors, such as the ASPP proteins (7), p63 and p73 (8), Mdm2 (30), and Hzf (31).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it should be noted that endogenously expressed Mdm2 can be found at promoters such as p21 (Minsky and Oren 2004;Arva et al 2005;Ohkubo et al 2006;White et al 2006;Tang et al 2008), negatively influencing p53's transcriptional output. The mechanism by which this occurs is unclear, but perhaps Mdm2 functions through recruitment of the histone deacetylases KAP1 (Wang et al 2005) and HDAC1 (Ito et al 2002), the disruption of HAT interactions with p53 (Ito et al 2002;Jin et al 2004), or the monoubiquitylation of histone H2B within the vicinity of the p53 RE (Minsky and Oren 2004).…”
Section: Transcriptional Regulation By P53mentioning
confidence: 99%